The microsomal triglyceride transfer protein inhibitor lomitapide improves vascular function in mice with obesity. Issue 4 (6th March 2022) - Munkhsaikhan, Undral; Kwon, Youngin; Sahyoun, Amal M.; Ait‐Aissa, Karima; Kassan, Adam; Kassan, Modar
Abstract: Objective: In this study, the effect of lomitapide, a microsomal triglyceride transfer protein inhibitor, on the cardiovascular function in obesity was investigated. Methods: Eight‐week‐old C57BL/6 mice were fed with high‐fat diet for 12 weeks in the presence and absence of lomitapide. Lomitapide was administered by gavage (1 mg/kg/d) during the last 2 weeks of high‐fat feeding. Body weight, blood glucose, body composition, and lipid profile were determined. Vascular function and endothelial function markers were studied in the aorta and mesenteric resistance arteries. Results: Lomitapide treatment reduced body weight in mice with obesity. Blood glucose, percentage of fat mass, total cholesterol, and low‐density lipoprotein levels were significantly reduced, and the percentage of lean mass was significantly increased after lomitapide treatment. The vascular response to sodium nitroprusside in the aorta and mesenteric arteries was similar among groups. However, the vascular response to acetylcholine was improved in the treated group. This was associated with decreased levels of vascular endoplasmic reticulum stress, inflammation, and oxidative stress. Conclusions: Treatment with lomitapide attenuated the increase in body weight in mice with obesity and restored the lipid profile and vascular function. These effects were accompanied by a decrease in inflammation and oxidative stress.